Komparasi Asean Sme Policy Index Dengan Rencana Strategis Dinas Perindustrian Dan Perdagangan Provinsi Kepulauan Riau - Sayed Fauzan Riyadi; Ryan Anggria Pratama (Kemudi, 2017)
This article compares two documents, ASEAN SMEs Policy Index 2014 with 2016-2021 Strategic Planning of Industrian dan Trade Office of Riau Islands Province. The aims is to see wether Micro, Small and Medium Enterprises (MSMEs) policy, especially for Small and Medium Industries, has been aligned with ASEAN Economic Community framework for SMEs development. From the analysis, it can be found that there are three field of comparison which show that those two documents aren not yet alligned: definition, informality and High-Growth Entrepreneurship orientation.